Chordin-Like 1 Improves Osteogenesis of Bone Marrow Mesenchymal Stem Cells Through Enhancing BMP4-SMAD Pathway - Liu, Tao; Li, Bo; Zheng, Xin-Feng; Jiang, Sheng-Dan; Zhou, Ze-Zhu; Xu, Wen-Ning; Zheng, Huo-Liang; Wang, Chuan-Dong; Zhang, Xiao-Ling; Jiang, Lei-Sheng (Frontiers in Endocrinology, 2019)
Chordin-like 1 (CHRDL1) is a secreted glycoprotein with repeated cysteine-rich domains, which can bind to BMPs family ligands. Although it has been reported to play important roles in several systems, the exact roles of CHRDL1 on human bone mesenchymal stem cells （hBMSCs） osteogenesis remain to be explored. The present study aimed to investigate the roles of CHRDL1 on the osteogenic differentiation of hBMSCs and the underlying molecular mechanisms. We found that CHRDL1 was upregulated during hBMSCs osteogenesis, and rhBMP-4 administration could enhance CHRDL1 mRNA expression in a dose and time dependent manner. Knockdown of CHRDL1 did not affect hBMSCs proliferation, but inhibited the BMP-4-dependent osteogenic differentiation, showing decreased mRNA expression levels of osteogenic markers and reduced mineralization. On the contrary, overexpression of CHRDL1 enhanced BMP-4 induced osteogenic differentiation of hBMSCs. Moreover, in vivo experiments by transplanting CHRDL1 gene modified hBMSCs into nude mice defective femur models displayed higher new bone formation in CHRDL1 overexpression groups, but lower new bone formation in CHRDL1 knockdown groups, compared with control groups. In consistent with the bone formation rate, there were increased CHRDL1 protein expression in new bone formation regions of defective femur in CHRDL1 overexpression groups, while reduced CHRDL1 protein expression in CHRDL1 knockdown groups compared with control groups. These indicate that CHRDL1 can promote osteoblast differentiation in vivo. Furthermore, the mechanisms study showed that CHRDL1 improved BMP-4 induced phosphorylation of SMAD1/5/9 during osteogenic differentiation of hBMSCs. Besides, promotion of osteogenic differentiation and the activation of SMAD phosphorylation by CHRDL1 can be blocked by BMP receptor type I inhibitor LDN-193189. In conclusion, our results suggested that CHRDL1 can promote hBMSCs osteogenic differentiation through enhancing the activation of BMP-4-SMAD1/5/9 pathway.